Ethnopharmacological Survey on - Klotoé, Jean robert; DOUGNON, T. VICTORIEN; Koudouvo, Koffi; ATEGBO, JEAN-MARC NOUNAGNON; LOKO, Frédéric; AKOEGNINOU, AKPOVI; AKLIKOKOU, Kodjo; DRAMANE, KARIM LAYE; Gbeassor, M. (My University, 2012)
Aims: Bleeding is the leading cause of early death and a post-traumatic major cause of maternal mortality worldwide. Although 80% of African people have used herbs to treat wounds, very little information is available about plants species with hemostatic properties. This study aims to contribute to a better knowledge of plants used for their hemostatic properties in southern Benin. Study Design: Ethnobotanical and survey study.Place and Duration of Study: Southern Benin in West Africa between January and June 2011. Methodology: Ethnopharmacological surveys were conducted from January to June 2011, with 66 traditional healers in Southern Benin using the method by Semi Structured Interview (SSI). Results: We surveyed 55 species of medicinal plants belonging to 28 families. The most used species were: Musa sapientum L., Jatropha multifida L., Rauvolfia vomitoria Afzel., Annona muricata L., Macrosphyra longistyla DC. And Newbouldia leavis P. Beauv. The use of these plants is more common in postpartum hemorrhages (45.8%), scarification (22%), circumcision (13%) and snake bites (7%). Preparations administered orally (56.8%) or locally (43.2%) are most often in the form of various extraction products (latex sap or juice (31.9%), aqueous decoction (22.7%), aqueous maceration (17.6%) or powder (13.5%). The plant parts most frequently used are: leaves (38.2%), bark (23.6%), roots (12.7%) and latex (11.9%). Conclusion: The extracts of these plants could therefore be an attractive option given the urgency posed by hemorrhages.
Keywords: Ethnopharmacological surveys; medicinal plants; bleeding; southern Benin.